The Effectiveness Of The Index Card Match Model On Students’ Learning Activeness And Motivation: An Experimental Study - Ajeng Uswatun Hasanah; Wan Jamaluddin; Uswatun Hasanah (Lembaga Riset dan Inovasi Almatani, 2026)
Learning activeness and learning motivation are two important factors that influence the success of the learning process. However, in classroom practice, these aspects often do not develop optimally due to the use of less varied and teacher-centered learning models. One alternative learning model that can be applied is the Index Card Match (ICM) model, which emphasizes students’ active involvement through matching question and answer cards. This study aimed to determine the effectiveness of the Index Card Match model on students’ learning activeness and learning motivation among eighth-grade students at SMPN 3 Way Pengubuan. The research employed a quantitative approach using an experimental method. Data were collected through non-test questionnaires based on a Likert scale that had been tested for validity and reliability. The learning activeness questionnaire consisted of 14 items (13 valid items; reliability coefficient = 0.708), while the learning motivation questionnaire consisted of 12 items (11 valid items; reliability coefficient = 0.645). Data analysis included prerequisite tests (normality and homogeneity) followed by hypothesis testing using the independent sample t-test. The results showed a significance value of < 0.05, indicating a significant difference between the groups. These findings demonstrate that the Index Card Match learning model has a positive effect on improving students’ learning activeness and learning motivation. Therefore, this model is recommended as an effective alternative learning strategy to enhance students’ participation, engagement, and motivation in the learning process.